Pengaruh Masuknya Pembaharuan Pemikiran Islam dalam Bidang Pendidikan - Adi Syahputra; Haidar Putra Daulay; Zaini Dahlan (Yayasan Rahmat Islamiyah, 2021)
Renewal is a necessity that the world from time to time undergoes changes that will not exist in the field of Islamic education. Good education will make an institution that develops and advances so that it is of high quality and produces significant educational goals. According to Abduh, Islamic education institutions need to have a photo that can bridge the two major cultural products in the world, namely Islam and the West. This discussion is important because it tries to construct the thoughts of thought leaders about education and its relevance to Islamic education, then critically analyzed through a historical perspective.Keywords : Renewal. Education. Islam